FACTORS CONTROLLING PETROGRAPHIC COMPOSITION OF NEOGENE TENGGARONG COALS-KUTAI BASIN-EAST KALIMANTAN - Binarko Santoso (Indonesian Mining Journal, 2016)
Petrographic composition of the Neogene Tenggarong coals in the Kutai Basin-East Kalimantan indicates its geological setting. The aim of this study is to obtain an understanding of the geologic aspects controlling the petrographic composition of the coals.Variation of type and rank in the coals was determined by petrographic examination of twenty-two samples. The coals are absolutely dominated by vitrinite, common liptinite and rare inertinite and mineral matter. Vitrinite macerals are dominated by detrovitrinite and telovitrinite. Cutinite and resinite are the dominant liptinite macerals in the coals. The inertinite macerals include semifusinite, inertodetrinite and sclerotinite. Clay and pyrite are the dominant mineral matters in the coals. The type differences largely reflect climatic influence and differences in peat conditions. Rank of the coals, in general, depends largely on the stratigraphic position. Reflectance measurements on the coals indicate that there is a slightly difference in rank. The coals are sub-bituminous rank (Rvmax of 0.40-0.47%). The change in vitrinite reflectance of the coals is due to the thicker cover/overburden on the high rank coals. Nevertheless, the vitrinite reflectance is higher in some coals in the Loa Kulu area (Rvmax of 0.48-0.57%) due to its stratigraphic position that is at the bottom of the sequence. The type and rank characteristics of the coals clearly influence the utilization. The coals are suited to utilize for direct combustion and therefore, the major utilization potential would be for power generation.